Safety maintenance procedure for mechanical and electrical works in high-rise buildings / Nurdiana Laila Zakaria - Zakaria, Nurdiana Laila (Faculty of Architecture, Planning and Surveying, 2013)
Safety procedure is an important thing to be measured while dealing with the mechanical and electrical maintenance works especially in high-rise building. To make sure the safety of the maintenance workers, the employers should play their roles to prevent and avoid their workers from injuries and accidents during the maintenance works. The safety procedure should be implemented before, during and after the maintenance works. The first objective of this research study is to study on the standards safety practice in mechanical and electrical maintenance works in high rise building. Second objective is to identify the best practice of safety maintenance procedure for mechanical and electrical works. Finally, this research will proposed a basic guideline of safety maintenance procedure for mechanical and electrical works. The stage of research methodology includes preliminary study, collection of data, analysis of data and report writing. In this study, the primary data is gathered from site observation, questionnaires and semi-structure interviews with the respondents. Meanwhile, the secondary data is gathered mainly from research paper, books, related articles and journals. The questionnaire is distributed to respondents in three (3) case studies which are Bangunan Darul Ehsan, Shah Alam, Bangunan Dewan Bandaraya Kuala Lumpur (DBKL), and Menara HeiTech Village UEP Subang Jaya. The semi-structure interview sessions were carried out face-to-face with the building maintenance person and also with the management person from Energy Commission. The study has revealed that the safety during the maintenance works in a moderate level to each case study.